Exports and Economic Development - Villanueva, Delano (IMF Working Papers; Working Paper ;, 1993)
A robust empirical determinant of long-term economic growth in many developing countries has been the expansion and diversification of the export sector. The latter, in turn, has been influenced by capital accumulation and economic growth. The growth model developed here explores this interdependence in the context of the 'new growth theory'. The analytical results are consistent with empirical regularities observed in the exports-economic growth linkages. The paper also derives a formula for the optimal rate of return to capital in the presence of learning effects and improvement of human resources brought about by export expansion and its interaction with saving and investment.